Racial disparities in colorectal cancer outcomes and access to care: a multi-cohort analysis - Riviere, Paul; Morgan, Kylie M.; Deshler, Leah N.; Demb, Joshua; Mehtsun, Winta T.; Martinez, Maria Elena; Gupta, Samir; Banegas, Matthew; Murphy, James D.; Rose, Brent S. (Frontiers in Public Health, 2024)
Introduction Non-Hispanic Black (NHB) Americans have a higher incidence of colorectal cancer (CRC) and worse survival than non-Hispanic white (NHW) Americans, but the relative contributions of biological versus access to care remain poorly characterized. This study used two nationwide cohorts in different healthcare contexts to study health system effects on this disparity. Methods We used data from the Surveillance, Epidemiology, and End Results (SEER) registry as well as the United States Veterans Health Administration (VA) to identify adults diagnosed with colorectal cancer between 2010 and 2020 who identified as non-Hispanic Black (NHB) or non-Hispanic white (NHW). Stratified survival analyses were performed using a primary endpoint of overall survival, and sensitivity analyses were performed using cancer-specific survival. Results We identified 263,893 CRC patients in the SEER registry (36,662 (14%) NHB; 226,271 (86%) NHW) and 24,375 VA patients (4,860 (20%) NHB; 19,515 (80%) NHW). In the SEER registry, NHB patients had worse OS than NHW patients: median OS of 57 months (95% confidence interval (CI) 55–58) versus 72 months (95% CI 71–73) (hazard ratio (HR) 1.14, 95% CI 1.12–1.15, p = 0.001). In contrast, VA NHB median OS was 65 months (95% CI 62–69) versus NHW 69 months (95% CI 97–71) (HR 1.02, 95% CI 0.98–1.07, p = 0.375). There was significant interaction in the SEER registry between race and Medicare age eligibility (p < 0.001); NHB race had more effect in patients <65 years old (HR 1.44, 95% CI 1.39–1.49, p < 0.001) than in those ≥65 (HR 1.13, 95% CI 1.11–1.15, p < 0.001). In the VA, age stratification was not significant (p = 0.21). Discussion Racial disparities in CRC survival in the general US population are significantly attenuated in Medicare-aged patients. This pattern is not present in the VA, suggesting that access to care may be an important component of racial disparities in this disease.